Evaluation of Sympathetic Response in Offsprings of Hypertensive and Normotensive Parents - Karmacharya, Poonam; Singh, Surjit; Tiwari, Indu (Journal of Nepal Health Research Council, 2020)
Background: Disturbances of the autonomic nervous system play a crucial role in the pathogenesis and clinical course of many diseases. Sympathetic response is an exaggerated response to stress. Studies have shown that enhanced sympathetic response to stress is an indication of prehypertensive states. Young offspring of hypertensive parents are a good model for assessing sympathetic reactivity prior to clinical hypertension. The aim of this study is to compare the sympathetic response in normotensive offspring of both hypertensive and normotensive parents.Methods: 100 young normotensives, non-smoking and healthy students (male and female) of Manipal College of medical science with a family history of hypertension and 100 young normotensives students, non-smoking and healthy with a negative family history of hypertension were enrolled in the study. Blood pressures at rest and after Isometric hand grip test and cold pressor test were measured. Statistical analysis was done to compare the blood pressure at rest and after isometric hand grip exercise and cold pressor test using independent t test.Results: A statistically significant increase in systolic and diastolic blood pressures were observed in normotensive offspring of hypertensive parents, compared to the normotensive offspring of normotensive parents indicating sympathetic overactivity after isometric hand grip exercise and cold pressor test (P<0.001). Conclusions: Normotensive offspring of hypertensive parents showed increase sympathetic reactivity after stress was given in the form of isometric hand grip exercise and cold pressor test. Thus, normotensive offspring of hypertensive parents are more likely to develop future hypertension and the risk is greater when both the parents were hypertensive.Keywords: Cold pressor test; Isometric hand grip test; Sympathetic reactivity.